PERLINDUNGAN HUKUM BAGI LENDER DAN BORROWER DALAM PENYELENGGARAAN FINTECHLENDING DI INDONESIA - Suhendar, Heris; Diniyanto, Ayon (MIH Unsoed, 2020)
The development of fintech lending in Indonesia has increased quite significantly.The number of registered fintech lending is 136 and licensed 25, bringing the total to 161.The existence of fintech lending in addition to providing benefits, also has the potential to bring risks to lenders and borrowers. Potential risks regarding the security and confidentiality of fintech lending user data and potential risk of non-performing financing (wanprestasi). This study is a normative legal research / doctrinal legal research using the statute and conceptual approach. This study material was obtained through library research (library research), then analyzed analytically for prescriptive examination and discussion. The results of the analysis are interpreted using systematic, grammatical and teleological interpretation methods. The results of the study concluded that, legal protection to avoid potential risks for users (lenders or borrowers) fintech lending can be done through preventive, persuasive and repressive steps. To support this step, legal instruments formed by the OJK include legal substance, legal structure and legal culture.